The Role of Personal Growth Initiative in Students’ Lives and Implications for Educational Counselors - Ferianti; Nurihsan, Juntika; Setiawati; Habibi, Muhammad Nur (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Personal growth initiative (PGI) were born from positive psychology, which plays a role in the development of students and their lives. However, currently, no systematic review specifically discusses previous research on the role of PGI in students' lives and what advice is given to educational counselors regarding students' PGI. Therefore, this research aims to review a systematic review of the role of PGI in students' lives and its implications for educational counselors. The systematic review method with the systematic review and meta-analysis (PRISMA) protocol was used to collect data. Data was obtained through the Scopus database using the article title